Utilization of Family Planning Contraceptives among Women inthe Coastal Area of South Buru District, Maluku, 2017 - Titaley, Christiana Rialine; Sallatalohy, Ninik (UI Scholars Hub, 2020)
Maluku Province is one among provinces in Indonesia with a contraceptive prevalence rate (CPR) lower than the national average. This study aimed toexamine factors associated with the utilization of family planning contraceptives among women of reproductive age living in the coastal area of South BuruDistrict, Maluku, Indonesia. Data were derived from a household health survey conducted in five subdistricts in South Buru, e.g., Namrole, Leksula, Waesama,Kapala Madan and Ambalau Subdistricts on November 2017 by the Faculty of Medicine, Pattimura University in Ambon. Information on contraceptive usewere collected from 390 married women aged 20 - 49 years. Bivariate and multivariate logistic regression analysis were employed to examine the factorsassociated with utilization of family planning contraceptives. This study found a low rate of utilization of family planning contraceptives (38.5%). The odds ofutilization modern contraceptive significantly reduced among women living in Ambalau and Leksula Subdistricts, aged 41 - 49 years, those who intend to havemore number of children, and with a low level of knowledge about family planning contraceptive methods.